2020
DOI: 10.3390/su12218925
|View full text |Cite
|
Sign up to set email alerts
|

Polish Consumers’ Response to Social Media Eco-Marketing Techniques

Abstract: This study attempts to verify whether green-marketing efforts of companies are recognised by the Polish customer in social media—a vital marketing communication channel. For businesses, this awareness carries important implications for the effectiveness and profitability of the eco-marketing campaigns. This study employed survey methodology, which was coupled with participant observation of online ecology-centred communities. It is shown that the economic aspect of green marketing is valued by customers and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Women, as fundamentally involved in various household activities, rank this value highly. The results obtained confirm research conducted in the retail trade industry (Bojanowska and Kulisz, 2020). Selected functional values for surveyed customers were predictors of their brand loyalty (Cunningham and De Meyer-Heydenrych, 2021).…”
Section: Results and Conclusionsupporting
confidence: 81%
“…Women, as fundamentally involved in various household activities, rank this value highly. The results obtained confirm research conducted in the retail trade industry (Bojanowska and Kulisz, 2020). Selected functional values for surveyed customers were predictors of their brand loyalty (Cunningham and De Meyer-Heydenrych, 2021).…”
Section: Results and Conclusionsupporting
confidence: 81%
“…As shown by the research, femininity is closely correlated with environmental protection [102]. The research by Bojanowska and Kulisz [103] proved that gender correlates with questions about the visibility of pro-ecological activities of companies, including the idea of "zero-waste" in social media. The study showed that women are more aware of the existence of "zero waste" and environmental campaigns in social media.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that women are more aware of the existence of "zero waste" and environmental campaigns in social media. Moreover, women perceive "zero waste" as a lifestyle [103]. Other researchers established a relationship between the gender of a brand and an environmental image [104].…”
Section: Discussionmentioning
confidence: 99%
“…Women display higher awareness of "zero-waste" and pro-ecological social-media campaigns. Overall, those who perceive "zero waste" as a lifestyle include women, who are more observant (Bojanowska and Kulisz, 2020). It was also found that the Internet and the availability of the opinions of others are decisive factors in the decision to purchase organic products, and women more frequently declare that they take into consideration opinions of other Internet users while making decisions to buy organic products (Maciaszczyk and Kocot, 2021).…”
Section: Discussionmentioning
confidence: 96%